Correction to: Calcareous nannofossil biostratigraphy of the Lower–Middle Pleistocene boundary of the GSSP, Chiba composite section in the Kokumoto Formation, Kazusa Group, central Japan, and implications for sea-surface environmental changes - Koji Kameo; Yoshimi Kubota; Yuki Haneda; Yusuke Suganuma; Makoto Okada (Progress in Earth and Planetary Science, 2020)
An amendment to this paper has been published and can be accessed via the original article.